Maneuvering Detection Using Multiple Parallel CUSUM Detector. (12th March 2018) - Liu, Hongqiang; Zhou, Zhongliang; Lu, Chunguang
Abstract : The switching model tracking algorithm based on hard decisions is an important method to solve the maneuvering target tracking problem. The use of Doppler velocity not only helps shorten the delay time of maneuvering detection but also provides information about the target motion model. A novel target maneuvering detection method named Multiple Parallel Cumulative Sum (M-CUSUM) for target multiple maneuvering models is proposed in this paper based on Doppler velocity. The main scheme of the proposed approach consists of the following: firstly, the problem framework of multiple model maneuvering detection is put forward; secondly, the statistic of acceleration is obtained through modeling the mapping relationship between Doppler velocity and the normal/tangential acceleration according to the geometry and kinematics; thirdly, the joint empirical distribution of the normal/tangential acceleration is obtained by the statistical experiment method and then the approximate joint probability distribution function of the normal/tangential acceleration is acquired by use of Gaussian Mixture Model (GMM) with Expectation Maximization (EM) algorithm; fourthly, it is taken as the prior information of target maneuvering which is introduced to the likelihood ratio of prediction measurement residual by the marginalization method; finally, the standard Cumulative Sum (CUSUM) detector is extended as Multiple Parallel CUSUM detector. Simulation results show that M-CUSUM detector has a smaller maneuver onset detection delay time compared with similar detectors and has the ability of pattern recognition of target maneuvers.